John K. Shellenberger correspondence - Shellenberger, John K., 1843?-
Chiefly post-Civil War letters to Shellenberger in response to his articles on the battle of Franklin, Tenn. Correspondents, many of whom participated in the battle, include Mendal Churchill, Joseph Conrad, E. C. Dawes, John Quincy Lane, William Gates Le Duc, Stephen D. Lee, David Sloane Stanley, Edward G. Whitesides, and Thomas John Wood. Also includes two letters of Gen. Jacob D. Cox pertaining to a promotion for Col. Emerson Opdycke for performance in the battle.
In part, handwritten transcripts.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Churchill, Mendal, -- -1902 -- Correspondence; Conrad, Joseph, -- 1830-1891 -- Correspondence; Cox, Jacob D. -- 1828-1900 -- Correspondence; Dawes, E. C. -- 1840- -- Correspondence; Lane, John Quincy -- Correspondence; Le Duc, William Gates, -- 1823-1917 -- Correspondence; Lee, Stephen D. -- 1833-1908 -- Correspondence; Opdycke, Emerson; Stanley, David Sloane, -- 1828-1902 -- Correspondence; Whitesides, Edward G. -- Correspondence; Wood, Thomas John, -- 1823-1906 -- Correspondence; Franklin, Battle of, Franklin, Tenn., 1864.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Army officers